Frequency and distribution of immunoglobulin containing plasma cells in ileum representing gut-associated - lymphatic tissues in the BCRDV - vaccinated broiler - Md. Zahirul Islam Khan; M. A. Masum; M.N.H. Siddiqia; M. Nasrin; N. Sultana (2012). 10 (1&2): 15-20, 2012)
Histological studies and development of immunoglobulin containing plasma cells in ileum representing gut-associated-lymphatic tissue of various group of broiler chickens vaccinated with Baby Chick Ranikhet Disease Vaccine (BCRDV) was carried out in the Department of Anatomy and Histology, Bangladesh Agricultural University, Mymensingh during January to October, 2011. A total of 24 day-old broiler chickens of both sexes were divided into two groups such as vaccinated and control. Vaccinated group of broiler chickens were vaccinated at third day through ocular route. It was observed that the villi of ileum were long and slender, lined by simple columnar cells with numerous goblet cells. Scattered lymphocytes and unorganized lymphatic nodules were present in the lamina propria and core of the villi. The frequency and distribution of lymphocytes in the lamina propria and intraepithelial lymphocytes were increased with concentration in vaccinated group. The length and width of mucosa were highest at D28. In the ileum of chickens, the IgA, IgG and IgM positive cells were found in the lamina propria, around the intestinal glands and in the core of the villi of both control and vaccinated group of chickens. The IgA positive cells were significantly (p<0.01) higher than IgG and IgM positive cells in all stages of study in each group of chickens.